Kebutuhan Air Irigasi Menggunakan Dua Metode Klasik dan Aplikasi Cropwat 8.0 Di D.I Kuranji - Hadie, Muhammad Shubhi Nurul; Hanifa, Azkia Hidayati (Universitas Andalas, 2024)
Calculation of Irrigation Water Requirements can be carried out using various methods, both several commonly used classification methods, as well as the application of new software-based methods and applications that are expected to simplify the calculation process with satisfactory results. This study aims to analyze the application of several methods for calculating irrigation water requirements for rice plants, especially in the Batang Kuranji Irrigation Area of ​​Padang City. The hydrological data used includes 15 years of data (2003-2020) taken from the Gunung Nago and Batu Busuk Rain Stations. The calculation methods used in this study are the Modified Penman Method, manual Penman Monteith, and the use of the CROPWAT 8.0 Application to calculate Potential Evapotranspiration (ETo), Plant Evapotranspiration (Etc), and irrigation water requirements (IR). Which obtained the ETo value of 3.556 mm/day using the CROPWAT 8.0 application, Modified Penman of 3.939 mm/day, and for Penman Monteith of 3.655 mm/day. Meanwhile, for the value of plant evapotranspiration (ETc) for CROPWAT 8.0, an average of 3.703 mm/day was obtained, Penman Modification 4.82 mm/day, and Penman-Monteith 5.56 mm/day. For the value of maximum irrigation water requirements using the CROPWAT 8.0 application, it reached 11.29 mm/day, which is the largest value found in April in the 2nd decade. Meanwhile, for Penman Monteith and Penman Modification, the results were 9.33 mm/day and 9.57 mm/day, respectively. The results of the calculation of irrigation water discharge requirements (Dr) were obtained from the three methods used, namely CROPWAT 8.0 of 1.307 lt/sec/ha, Penman Modification of 1.342 lt/sec/ha, and for manual Penman-Monteith of 1.302 lt/sec/ha. The results of this study show the importance of using technology in efficient water resource management to support agricultural productivity, and provide recommendations for the use of more accurate soil data so that the analysis results are more reliable.